Adaptasi dan Tipologi Hotel Maison Wilhelmina di Kawasan Heritage Braga, Bandung - Safanisa Aurellia; Fadhia Rahma Aulya (GLOBAL SCIENTS PUBLISHER, 2026)
The Braga area is a historical artifact of colonial architectural development in the city of Bandung. One of the buildings that has undergone a transformation in function is the Maison Wilhelmina Hotel, which now operates as a boutique hotel through a process of adaptive reuse. This study aims to evaluate the extent of the success of this transformation using architectural criticism methods, namely doctrinal criticism and typical criticism. Through doctrinal criticism, the building is assessed based on the principles of preservation and tropical architecture, while typical criticism is used to analyze the building's suitability with modern boutique hotel standards. The results of the analysis show harmony in terms of the facade, but there are internal circulation constraints due to limited land that affects the comfort of private spaces.